New combinations in Stenostelma (Apocynaceae—Asclepiadoideae) and two novel species from South Africa - Bester, Stoffel P.; Nicholas, Ashley (Phytotaxa, 2018)
Two new combinations are made for taxa that were previously attributed to the genus Schizoglossum and are now placed in the genus Stenostelma. Included is the typification of Stenostelma capense, S. carinatum, S. corniculatum, S. eustegioides and S. periglossoides. Two new species, Stenostelma ligulatum and S. urceolatum, both with restricted distributions, are described here. Preliminary conservation assessments (Red List status) for the newly described taxa are provided.